Subjective well-being in muallaf - M. Yusuf Effendi (Journal of Advanced Guidance and Counseling, 2022)
Purpose - This research is to find out the subjective well-being of muallaf where the focus of this research is the subjective well-being of muallaf.Method - The informants in this study were three primary informants, consisting of one student muallaf, two housewives muallaf. Data collection was carried out by interview and documentation methods. This study uses a phenomenological study method approach with Interpretative Phenomenological Analysis data analysis techniques. The credibility of the data used by researchers was tested using source triangulation.Result - The results and conclusions of this study are that each muallaf participant experiences subjective well-being in himself. Subjective well-being experienced by all muallaf participants in this study has a different picture. This happened because in deciding to become a muallaf, all participants had their own approaches and perspectives on the events they experienced before.Implication - Each muallaf participant in this study has various life satisfaction, positive affect and negative affect, all of which are subjective well-being processes of every participant muallaf.Originality - This research is presented concerning religious guidance services for deaf individuals.***Tujuan - Penelitian ini bertujuan untuk mengetahui kesejahteraan subjektif mualaf dimana fokus penelitian ini adalah kesejahteraan subjektif mualaf.Metode - Informan dalam penelitian ini adalah 3 orang informan primer, yang terdiri dari 1 orang mahasiswa mualaf, 2 orang ibu rumah tangga mualaf. Pengumpulan data dilakukan dengan metode wawancara dan dokumentasi. Penelitian ini menggunakan pendekatan metode studi fenomenologi dengan teknik analisis data Interpretative Phenomenological Analysis. Kredibilitas data yang digunakan peneliti diuji dengan menggunakan triangulasi sumber.Hasil - Hasil dan kesimpulan dari penelitian ini adalah setiap partisipan mualaf mengalami subjective well-being dalam dirinya. Subjective well-being yang dialami oleh seluruh partisipan mualaf dalam penelitian ini memiliki gambaran yang berbeda-beda. Hal ini terjadi karena dalam memutuskan untuk menjadi seorang mualaf, semua partisipan memiliki pendekatan dan cara pandang masing-masing terhadap peristiwa yang dialaminya sebelumnya.Implikasi - Setiap partisipan mualaf dalam penelitian ini memiliki kepuasan hidup, afek positif dan afek negatif yang berbeda-beda, yang kesemuanya merupakan proses subjective well-being dari setiap partisipan mualaf.Orisinalitas - Penelitian ini disajikan mengenai layanan bimbingan keagamaan bagi individu tuna rungu.